# Homework Help: How do I integrate this?

1. Oct 30, 2006

### b2386

How do I integrate this? It is not of any form with which I am familiar.

$$\int_{-\infty}^{\infty}x^2e^{-b^2x^2}dx$$

2. Oct 30, 2006

$$\int_{-\infty}^{\infty}x^2e^{-b^2x^2}dx = 2\int_{0}^{\infty} x^2e^{-b^2x^2}dx$$ because the function is even.

Then use integration by parts.

3. Oct 30, 2006

### quasar987

4. Oct 31, 2006

### b2386

Thanks for the replies.

hmmm...

Quasar, could you please explain the steps in your link. I looked over it but do not fully understand what is going on. Lets start here: $$\int_{-\infty}^{\infty} e^{-\frac{x^2}{2\sigma^2}} = \sqrt{2 \pi \sigma^2}$$

How do we know this?

Last edited: Oct 31, 2006
5. Oct 31, 2006

### quasar987

By parts it's u=x, dv=xexp{...}dx

Of course if you do not know a priori that

$$\int_{-\infty}^{\infty} e^{-\frac{x^2}{2\sigma^2}} = \sqrt{2 \pi \sigma^2}$$,

this complicates things, as you won't be able to do the integral by parts either. Is this for a QM course? In this case, it is probably assumed that you know the result of the above integral. If you don't and want to know how to do it, here it is roughly. It's a beautiful and ingenious trick, watch. If I remember correctly, it goes like...

$$\int_{-\infty}^{+\infty} e^{-b^2 x^2}dx=\sqrt{\left( \int_{-\infty}^{+\infty} e^{-b^2 x^2}dx \right)^2} = \sqrt{\left( \int_{-\infty}^{+\infty} e^{-b^2 x^2}dx \right)\left( \int_{-\infty}^{+\infty} e^{-b^2 y^2}dy \right)}=\sqrt{ \int_{-\infty}^{+\infty}\int_{-\infty}^{+\infty} e^{-b^2( x^2+y^2)}dx dy }$$

Now switch to polar coordinates: r²=x²+y², $dxdy=rdrd\theta$ r going from 0 to infinity, theta going from 0 to 2pi [in order to cover the whole R² plane]:

$$\int_{-\infty}^{+\infty} e^{-b^2 x^2}dx = \sqrt{\int_{0}^{+\infty}\int_{0}^{+2\pi} re^{-b^2( r^2)}dr d\theta }=\sqrt{2\pi\int_{0}^{+\infty}re^{-b^2( r^2)}dr}$$

Set u=b²r² ==> du=2rb²dr ==>rdr=du/2b²:

$$\int_{-\infty}^{+\infty} e^{-b^2 x^2}dx=\sqrt{\frac{\pi}{b^2}\int_{0}^{+\infty}e^{-u}du} = \sqrt{\frac{\pi}{b^2}\left[-e^{-u}\right]_0^{+\infty}}= \sqrt{\frac{\pi}{b^2}\left[0-(-1)\right]} = \sqrt{\frac{\pi}{b^2}}$$

Phew that was longer than I tought it would be! :yuck:

6. Nov 2, 2006

### SNOOTCHIEBOOCHEE

Tabular integration is the easiest method here. when you think your gunna use integration by parts, if one of the functions (when differentiated many times) goes to zero, then tabular integration will work. just look it up. its easy enough to understand